Impact of Early Clinical Exposure on First-year Medical Undergraduates: Student’s Perspective - Kusum Singla; Manju Chenicherry; Bishamber D Toora; Ritu Sharma (Journal of Medical Academics)
Introduction: Early clinical exposure (ECE) as a teaching method is a very significant element of competency-based medical education (CBME) introduced by the Medical Council of India (MCI) in 2019. In the traditional curriculum, teacher-centered classes with a vast syllabus covered in a short period in the first year without any clinical correlation make the subject dry and uninteresting. ECE helped the students recollect their relevant basic science knowledge and establish the bridge between the basic concepts and the clinical knowledge. Also helps in improving learning and recollecting knowledge, which is very important to transform medical students into competent physicians of first contact. ECE sessions improve their academic strength and help improve both communicable and clinical skills that help make the undergraduates more confident. Aim: To evaluate the first-year MBBS students’ perception of the impact of ECE on their overall academic improvement and learning process. Results and discussion: A total of 74.2% of students think that more and more topics should be included in the ECE for better understanding and retention of the topic as 83% find ECE very useful in the first year and an important part of their education. However, 73.9% of students also commented that ECE should be conducted in a hospital setup compared to the classroom or community setup. Conclusion: From the present study, we can conclude that ECE is a better learning tool for learners compared to a traditional curriculum. Students enjoy the ECE part as it makes their basic subjects more interesting and relevant, although further research on the large number of students can be useful.